Biodegradable Zn–Sr alloy for bone regeneration in rat femoral condyle defect model: In vitro and in vivo studies - Bo Jia; Hongtao Yang; Zechuan Zhang; Xinhua Qu; Xiufeng Jia; Qiang Wu; Yu Han; Yufeng Zheng; Kerong Dai (Bioactive Materials, 2021)
Bone defects are commonly caused by severe trauma, malignant tumors, or congenital diseases and remain among the toughest clinical problems faced by orthopedic surgeons, especially when of critical size. Biodegradable zinc-based metals have recently gained popularity for their desirable biocompatibility, suitable degradation rate, and favorable osteogenesis-promoting properties. The biphasic activity of Sr promotes osteogenesis and inhibits osteoclastogenesis, which imparts Zn–Sr alloys with the ideal theoretical osteogenic properties. Herein, a biodegradable Zn–Sr binary alloy system was fabricated. The cytocompatibility and osteogenesis of the Zn–Sr alloys were significantly better than those of pure Zn in MC3T3-E1 cells. RNA-sequencing illustrated that the Zn-0.8Sr alloy promoted osteogenesis by activating the wnt/β-catenin, PI3K/Akt, and MAPK/Erk signaling pathways. Furthermore, rat femoral condyle defects were repaired using Zn-0.8Sr alloy scaffolds, with pure Ti as a control. The scaffold-bone integration and bone ingrowth confirmed the favorable in vivo repair properties of the Zn–Sr alloy, which was verified to offer satisfactory biosafety based on the hematoxylin-eosin (H&E) staining and ion concentration testing of important organs. The Zn-0.8Sr alloy was identified as an ideal bone repair material candidate, especially for application in critical-sized defects on load-bearing sites due to its favorable biocompatibility and osteogenic properties in vitro and in vivo.